Use of a multi‐electrode radiofrequency balloon catheter to achieve pulmonary vein isolation in patients with paroxysmal atrial fibrillation: 12‐Month outcomes of the RADIANCE study. (23rd April 2020) - Dhillon, Gurpreet Singh; Honarbakhsh, Shohreh; Di Monaco, Antonio; Coling, Ann Elizabeth; Lenka, Kernerová; Pizzamiglio, Francesca; Hunter, Ross J.; Horton, Rodney; Mansour, Moussa; Natale, Andrea; Reddy, Vivek; Grimaldi, Massimo; et al.
Abstract: Background: The RADIANCE first‐in‐man study evaluated acute (3‐month) safety and design concept in terms of utility of a new multi‐electrode radiofrequency (RF) balloon catheter (HELIOSTAR, Biosense Webster) to achieve pulmonary vein isolation (PVI). After study conclusion, a subset of patients was followed up to 12 months. Methods: Patients with drug refractory paroxysmal atrial fibrillation were enrolled. Neurological assessment, cardiac and cerebral magnetic resonance imagings were performed pre and post procedure. Ablation was delivered at 15 Watts to each PV for 60 seconds (electrodes adjacent to the posterior wall limited to 20 seconds). Adenosine or isoproterenol was administered to confirm PVI. Esophageal endoscopy was performed 48 hours post procedure. Patients were clinically followed up for 12 months. Results: Thirty‐nine patients underwent catheter ablation from four centers. Mean age was 60.7 ± 10.0 years with 23 (57.5%) being male. Confirmation of PVI was performed in all PVs treated (152/152). Confirmation of isolation after one delivery was performed solely on 137 of 152 PVs of which 79.6% (109/137) achieved isolation with a single delivery of RF energy. Acute PV reconnection was seen in 4.6% (7/150) of PVs. Freedom from documented atrial arrhythmia at 12 months in those followed up was 86.4% (32/37). A total of 75.7% (28/37) of patients were free from atrial arrhythmia and off antiarrhythmic medications. Conclusion: The HELIOSTAR RF balloon catheter allows for rapid and safe PVI with majority of PVs only requiring one application.